Young Martian crater Gratteri and its secondary craters. Issue 7 (2nd July 2016) - Quantin, Cathy; Popova, Olga; Hartmann, William K.; Werner, Stephanie C.
Abstract: In response to questions that have been raised about formation and effects of secondary craters on crater chronometry techniques, we studied properties of the secondary crater field around the young Martian primary ray crater Gratteri (diameter 7 km). The crater has an estimated age of 1 to 20 Myr, based on counts of small craters on flat interior surface, consistent with a likely age for a young crater its size (Hartmann et al., 2010). The following are among our findings: (1) We identify an unusual class of craters we call "rampart secondaries" which may suggest low‐angle impacts. (2) We measure size distributions of secondaries as a function of distance from Gratteri and used these data to reconstruct the mass‐velocity distribution of ejecta blasted out of Gratteri. Our data suggest that crater density in rays tends to peak around 120–230 km from Gratteri (roughly 20–30 D ) and reaches roughly 30–70 times the interray crater density. (3) Comparable total numbers of secondaries form inside rays and outside rays, and about half are concentrated in clusters in 2% of the area around Gratteri, with the others scattered over 98% of the area out to 400 km away from Gratteri. (4) In the old Noachian plains around Gratteri, secondaries have minimal effect on crater chronometry. These results, along with recently reported direct measurements of the rate of formation of 10 m to 20 m primaries on Mars (Daubar et al., 2013), tend to negate suggestions that the numbers and/or clustering of secondaries destroy the effectiveness of crater counting as a chronometric tool. Key Points: We studied properties of the secondary crater field around the young primary ray crater Gratteri Crater density in rays tends to peak around 120–230 km from Gratteri In old terrains, secondaries have minimal effect on crater chronometry